Upaya Meningkatkan Hasil Belajar Pendidikan Kewarganegaraan Dengan Menerapkan Model Pembelajaran Jigsaw - Kasmunir Kasmunir (JURNAL GLOBAL EDUKASI, 2017)
Abstract: This research aims to improve the learning outcomes of Citizenship Education on cooperation materials of Southeast Asian countries by applying Jigsaw learning model. Subjects in this study were the students of class VI SD Negeri 010097 Selawan distrcit Eastern Kisaran City academic year 2016/2017 amounted to 30 students. The results obtained that the results of the learning process after research efforts to improve learning outcomes by applying the model of learning Jigsaw material Cooperation South East Asian countries Citizenship education lessons reached an average value of 72.33 in cycle I. After motivated conducted research through cycle II average value average to 83.83. The learning outcomes in cycle I reached the classical learning completeness of 76.75% after cycle II was done reflection and the 90% classical completeness learning recommendation. It can be concluded that the learning outcomes of Citizenship Education on the cooperation materials of Southeast Asian countries are increasing by applying Jigsaw learning model. Keywords: jigsaw, Southeast Asia, cooperation Abstrak: Penelitin ini bertujuan untuk meningkatkan hasil belajar Pendidikan Kewarganegaraan pada materi kerjasama negara-negara Asia Tenggara dengan menerapkan model pembelajaran Jigsaw. Subjek dalam penelitian ini adalah siswa kelas VI SD Negeri 010097 Selawan kec. Kota Kisaran Timur TP. 2016/2017 berjumlah 30 siswa. Hasil penelitian diperoleh bahwa hasil proses belajar setelah penelitian upaya meningkatkan hasil belajar dengan menerapkan model pembelajaran Jigsaw materi Kerjasama Negara-Negara Asia Tenggara pelajaran Pendidikan Kewarganegaraan mencapai nilai rata-rata 72,33 pada siklus I. Setelah termotivasi dilakukan penelitian melalui siklus II nilai rata-rata menjadi 83,83. Hasil belajar pada siklus I mencapai ketuntasan belajar klasikal sebesar 76,75% setelah siklus II dilakukan refleksi dan rekomendasi ketuntasan belajar klasikal mencapai 90%. Dapat disimpulkan hasil belajar Pendidikan Kewarganegaraan pada materi kerjasama negara-negara Asia Tenggara meningkat dengan menerapkan model pembelajaran Jigsaw. Kata kunci: jigsaw, Asia Tenggara, kerjasama